Potential Association of Strongyloides stercoralis and its effectivity against Type 2 Diabetes Mellitus: A Systematic Review of Scientific Attestation - Alimpolos, Jean A.; Martinez, Christian Ray A.; Morris, Navy May G.; Solano, Roel Nickelson P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The association of Strongyloides stercoralis in Type 2 Diabetes mellitus has put on a spotlight on various researchers after the discovery of S. stercoralis's capability to conduct immunomodulation through lowering the production and release of cytokines, all of which provide a contradictory action towards the development of T2DM. T2DM results from a high number of macrophages that secrete cytokines and chemokines abnormally, which affects the B-pancreatic cells and leads to insulin resistance. However, regardless of this information, the linkage of the immunomodulation mechanism of S. stercoralis infection against T2DM still needs clarification and further validation. Thus, this systematic review was conceptualized to identify if there is a direct association between S. stercoralis and T2DM, including the effects of the helminth on patients with such a disease, and the underlying factors related to this relationship. Studies for the review were collected in the following databases: PubMed, ProQuest, Wiley, Open Access Theses and Dissertations (OATD), Internet Archive Scholars, and Elsevier. The 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria was utilized to identify and screen eligible studies for review and among the chosen articles, three have suggested a direct association between S. stercoralis infection and T2DM, while two studies proved the absence of an association by statistical and clinical characteristics. These limited findings and conflicting evidence for a direct link between S. stercoralis and T2DM may indicate that the comorbidity of both factors points more toward an indirect relationship.